IMMUNOHISTOCHEMICAL EXAMINATION OF LUNG TISSUE CHANGES IN POST-COVID SYNDROME (International Conference on Scientific Research in Natural and Social Sciences, 2025)
As material for the article, a number of cases were taken in the Department of Adult Pathology and Biopsy Diagnosis of the Republican Center for Pathological Anatomy during 2020-2022, and the diagnosis of coronavirus infection was confirmed on the basis of clinical and morphological data. An analysis of clinical and laboratory data of patients who died of COVID-19 was obtained.